KEIKUTSERTAAN WANITA PASANGAN USIA SUBUR DALAM PROGRAM KELUARGA BERENCANA - Endah Wahyuningtias; Yurni Suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine the participation of women of childbearing age couples in the family planning program in Jorong Koto Gadang Jaya. The research method used is descriptive qualitative. Primary and secondary data types were obtained from Nagari Preparation Koto Gadang Jaya and PUSTU Koto Gadang Jaya. Based on the research, it is concluded that (1) women of childbearing age couples in Jorong Koto Gadang Jaya have a fairly good knowledge of the family planning program (2) not all women of childbearing age have joined the family planning program, especially young families (3) many couples fertile children who have participated in the family planning program but are not satisfied if they only have two children, so they still have more than two children.